Confrontation between Liberals and Radicals in Amy Waldman’s The Submission - Dhobi, Saleem (Pursuits: A Journal of English Studies, 2024)
The paper explores the repercussions of 9/11 in the diversity of the United States of America as portrayed in Amy Waldman’s The Submission published in the aftermath of 9/11 based on the cultural conflicts inherent in American culture. I unfold the problems the minority Muslims experience because of the 9/11 attacks on the US. The implications of the attacks on the intercultural relations of the minorities with the majority community reveal that the prevailing biases against Muslims and Islam as depicted in the text become obstacles to cultural harmony and integrity in American culture. The setbacks Muslims face in the aftermath of 9/11 make the principle of multiculturalism questionable. The paper has investigated into the cultural variables including traditions, behaviors, beliefs and practices of the respective ethnicities particularly American and Muslim in the United States. Such factors have influenced the opinions of both common Americans and the authorities to deal with the people having differences in the aftermath of the 9/11 attacks. Consequently, the liberals including Mo Khan and Claire from both American culture and Muslim minority are forced to suffer the backlash.